Practical training report: Sarawak Foundation / Mohamad Anuar Sepe - Sepe, Mohamad Anuar (Universiti Teknologi MARA, Sarawak, 2015)
The Sarawak Foundation was established under the Sarawak Foundation Ordinance as a Statutory Body on 27 May 1971. Their objectives as in the Ordinance are: 1. To grant scholarships or to provide financial assistance of any form to any person born in Sarawak, in particular, and to any Malaysian citizen, in general, to pursue their education in schools, colleges, universities or institutions of higher learning within Malaysia or abroad on such terms and conditions as the Board deems fit or proper; 2. Actively to promote improvement of opportunities for education for the peoples of Sarawak in particular and Malaysia in general, both locally and in any institution of higher learning throughout the world, but especially the Universities in Malaysia. 3. To grant, and arrange for the award by other bodies of, scholarships or other educational assistance for the peoples of Sarawak or any Malaysian citizen whenever it deems fit to do so;4. To give assistance and provide relief, to any person whose circumstances are, in the opinion of the Board, considered to be deserving of such assistance or relief;5. To provide assistance, by way of loans, grants or otherwise, to organizations or institutions which are organized and governed for scientific, medical, educational, welfare, social or charitable purposes;6. To make contribution and provide assistance towards the relief of national emergencies or calamities.